2021
DOI: 10.1093/cid/ciab583
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted Drug Resistance Among Human Immunodeficiency Virus (HIV)-1 Diagnoses in the United States, 2014–2018

Abstract: Background Transmitted HIV drug resistance can threaten the efficacy of antiretroviral therapy (ART) and preexposure prophylaxis (PrEP). Drug resistance testing is recommended at entry to HIV care in the United States and provides valuable insight for clinical decision-making and population-level monitoring. Methods We assessed transmitted drug resistance-associated mutation (TDRM) prevalence and predicted susceptibility to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 36 publications
5
37
0
Order By: Relevance
“…A study that included TDR prevalence data from 2001 to 2017 in China estimated that TDR prevalence was 4.1% ( 9 ), which is consistent with the results of this study. Reports on drug resistance testing from the WHO revealed that between 2014 and 2019, the median rate of transmission-resistant drugs was 4.1% in Southeast Asia, 6.0% in Sub-Saharan Africa, 9.1% in Latin America, 8.5% in Europe, and 14.2% in North America ( 10 ). Conversely, the prevalence of TDR was much higher in Europe and North America, which was consistent with the longer existence and variety of antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that included TDR prevalence data from 2001 to 2017 in China estimated that TDR prevalence was 4.1% ( 9 ), which is consistent with the results of this study. Reports on drug resistance testing from the WHO revealed that between 2014 and 2019, the median rate of transmission-resistant drugs was 4.1% in Southeast Asia, 6.0% in Sub-Saharan Africa, 9.1% in Latin America, 8.5% in Europe, and 14.2% in North America ( 10 ). Conversely, the prevalence of TDR was much higher in Europe and North America, which was consistent with the longer existence and variety of antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular monitoring results of newly diagnosed individuals in China showed that the most common mutations in patients’ resistance to NNRTI were E138G and V179E ( 12 ). Moreover, E138K was found to be the most common mutation in HIV-1 patients resistant to NNRTI in the US, according to an analysis of TDR from 2014 to 2018 ( 10 ). The impact of the combination of E138 and V179 on both NNRTI susceptibility and virologic outcome in patients deserves investigation.…”
Section: Discussionmentioning
confidence: 99%
“…). The proportion of countries meeting the target of having at least 5% of patients on secondline ART increased from 45% (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) in 2017 to 56% (14 of 25) in 2020. Overall, most countries reported sub-optimal performance in preventing HIVDR, indicating the need to strengthen the quality and monitoring systems and implement sustainable solutions.…”
mentioning
confidence: 99%
“…Within this population from the United States (US), TDR was more commonly attributable to nonnucleoside reverse transcriptase inhibitor (NNRTI) resistance-associated mutations (RAMs) ( 9 ). A more recent study conducted in PLWH in the US from 2014 to 2018 estimated that the prevalence of NNRTI mutations was 12% ( 10 ). Studies have documented a progressive increase in the prevalence of TDR across several geographic regions ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study conducted in PLWH in the US from 2014 to 2018 estimated that the prevalence of NNRTI mutations was 12% ( 10 ). Studies have documented a progressive increase in the prevalence of TDR across several geographic regions ( 9 12 ). Moreover, changing practices in ART may contribute additional mutations to TDR, particularly for NNRTIs ( 13 ).…”
Section: Introductionmentioning
confidence: 99%